Design of a company-engagement model for procurement and supply management classes - Remko I. van Hoek; Dominique Lebigot (Logistics, 2023)
Background: There are opportunities to enrich procurement and supply management classes to be more international and to engage with industry more deeply. Methods: Using a design science method this paper develops a course design for teaching procurement that enriches existing approaches to company engagement in courses. Results: Beyond the use of stand-alone guest lectures, case studies, or in-company projects, the design involved semester-long collaboration around core topics for the course, involving company lectures and multiple student projects aligned with the course topics, engaging multiple levels of managers from around the globe. Based upon an evaluation of the first-year collaboration, improvements were identified that were implemented in year two of the collaboration. Conclsuions: The design brings course learning into a real-world context and supports student skill development through project work.
Keywords: 650; collaborative learning; company engagement; education; guest lectures